The many faces of populism current perspectives - Wejnert, Barbara; Woods, Dwayne (Emerald, 2014)
Populism comes in many guises. Both Berlusconis personalization of politics and the Northern Leagues anti-immigrant regionalist movement are viewed as examples of the phenomenon of populism. A type of left-wing populism embodied by Hugo Chavez swept across Latin America. Insurgent and anti-system movements and parties in places as different as the Netherlands, India, Norway, Thailand, Russia and the United States have experienced what have been labeled populists movements. Such varied manifestations beg the question: what is populism? The objective of this edited volume is to provide an answer by examining "the many faces of populism." The unifying element across the different explorations of the phenomenon of populism is that there is a shared genus that allows for a typology of the different faces of populism and a demarcation of what is not a form of populism.
Keywords: Political Science -- Political Ideologies -- General.; Political ideologies.; Political activism.; Political structure & processes.; Populism.; elektronické knihy; electronic books